2017
DOI: 10.1002/mnfr.201700446
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to Peanut, Soybean, and Other Legumes: Recent Advances in Allergen Characterization, Stability to Processing and IgE Cross‐Reactivity

Abstract: Peanut and soybean are members of the Leguminosae family. They are two of the eight foods that account for the most significant food allergies in the United States and Europe. Allergic reactions to other legume species can be of importance in other regions of the world. The major allergens from peanut and soybean have been extensively analyzed and members of new protein families identified as potential marker allergens for symptom severity. Important recent advances concerning their molecular properties or cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
114
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 95 publications
0
114
0
16
Order By: Relevance
“…The peanut allergenic individuals also possess an 86% risk of being sensitized toward other nut allergies due to cross-reactivity Maloney, Rudengren, Ahlstedt, Bock, & Sampson, 2008). Cross-reactivity is an important consideration for peanut sensitized individuals as peanut proteins are homologous to proteins in other nuts, seeds, and vegetables (Cabanillas, Jappe, & Novak, 2018;Elizur, Bollyky, & Block, 2017), thus making dietary management more complex for allergic individuals. Interestingly, non-homologous peanut allergens also show different levels of cross-reactivity with each other due to similar exposed IgE epitopes on the surface (Bublin et al, 2013).…”
Section: Molecular Characteristics Of Peanut Allergensmentioning
confidence: 99%
“…The peanut allergenic individuals also possess an 86% risk of being sensitized toward other nut allergies due to cross-reactivity Maloney, Rudengren, Ahlstedt, Bock, & Sampson, 2008). Cross-reactivity is an important consideration for peanut sensitized individuals as peanut proteins are homologous to proteins in other nuts, seeds, and vegetables (Cabanillas, Jappe, & Novak, 2018;Elizur, Bollyky, & Block, 2017), thus making dietary management more complex for allergic individuals. Interestingly, non-homologous peanut allergens also show different levels of cross-reactivity with each other due to similar exposed IgE epitopes on the surface (Bublin et al, 2013).…”
Section: Molecular Characteristics Of Peanut Allergensmentioning
confidence: 99%
“…36 Lupin, peanut and soya allergy are 3 of the main allergens encountered in the legume family but many other novel allergens in this family are appearing (lentil, chickpea, green bean or pea) and these allergens, plus the effect of processing on their allergenicity need further investigation. 36 Lupin, peanut and soya allergy are 3 of the main allergens encountered in the legume family but many other novel allergens in this family are appearing (lentil, chickpea, green bean or pea) and these allergens, plus the effect of processing on their allergenicity need further investigation.…”
Section: Important But Needs Workmentioning
confidence: 99%
“…Legume allergy is complex to diagnose and manage. 36 Lupin, peanut and soya allergy are 3 of the main allergens encountered in the legume family but many other novel allergens in this family are appearing (lentil, chickpea, green bean or pea) and these allergens, plus the effect of processing on their allergenicity need further investigation. Cousin et al 37 demonstrated that using cluster analysis, distinct cluster of possible cross-reactions between tree nut, peanut and legumes exist, with those suffering from eczema, showing the highest rates of cross-reactions between these 3 aller-…”
Section: Important But Needs Workmentioning
confidence: 99%
“…Our study focused on Ara h 3, since it has been described as a major allergen in specific allergic study populations [2, 20, 21]. However, further studies would be necessary to analyze if similar results can be achieved for other allergens from peanut.…”
mentioning
confidence: 99%
“…Up to now, 16 allergens from peanut have been described and officially registered [2]. Peanuts are frequently subjected to thermal processing prior to consumption, and the method used for this can impact on the allergenicity of peanut.…”
mentioning
confidence: 99%